2013
DOI: 10.1021/ja407778a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Turn-On Ammonia Sensing Enabled by High-Temperature Fluorescence in Metal–Organic Frameworks with Open Metal Sites

Abstract: We show that fluorescent molecules incorporated as ligands in rigid, porous metal-organic frameworks (MOFs) maintain their fluorescence response to a much higher temperature than in molecular crystals. The remarkable high-temperature ligand-based fluorescence, demonstrated here with tetraphenylethylene- and dihydroxyterephthalate-based linkers, is essential for enabling selective and rapid detection of analytes in the gas phase. Both Zn2(TCPE) (TCPE = tetrakis(4-carboxyphenyl)ethylene) and Mg(H2DHBDC) (H2DHBDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
243
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(249 citation statements)
references
References 28 publications
6
243
0
Order By: Relevance
“…For example, Dincaˇ et al reported two MOFs [Zn 2 (tcpe)(H 2 O) 2 ]·4DEF and [Mg(H 2 dhbdc)(DMF) 2 ] (H 4 tcpe = tetrakis(4‐carboxyphenyl)ethylene, DEF = N , N ‐diethylformamide, H 4 dhbdc = 2,5‐dihydroxybenzene‐1,4‐dicarboxylic acid) showing shifts of emission wavelengths upon interaction with ammonia at 100 °C ( Figure 9 ). 96 [Zn 2 (tcpe)] shows staggered 2D layers constructed from paddle‐wheel shaped Zn 2 (RCOO) 4 clusters linked by tcpe 4− ligands, and is permanently porous with BET surface area of 317 m 2 g −1 . [Mg(H 2 dhbdc)] is constructed from 1D Mg 2 (RCOO) 4 chain linking by H 2 dhbdc 2− linkers in an alternative manner, showing 1D channel about 5.3 × 5.3 Å 2 .…”
Section: Coordinative Guestsmentioning
confidence: 99%
“…For example, Dincaˇ et al reported two MOFs [Zn 2 (tcpe)(H 2 O) 2 ]·4DEF and [Mg(H 2 dhbdc)(DMF) 2 ] (H 4 tcpe = tetrakis(4‐carboxyphenyl)ethylene, DEF = N , N ‐diethylformamide, H 4 dhbdc = 2,5‐dihydroxybenzene‐1,4‐dicarboxylic acid) showing shifts of emission wavelengths upon interaction with ammonia at 100 °C ( Figure 9 ). 96 [Zn 2 (tcpe)] shows staggered 2D layers constructed from paddle‐wheel shaped Zn 2 (RCOO) 4 clusters linked by tcpe 4− ligands, and is permanently porous with BET surface area of 317 m 2 g −1 . [Mg(H 2 dhbdc)] is constructed from 1D Mg 2 (RCOO) 4 chain linking by H 2 dhbdc 2− linkers in an alternative manner, showing 1D channel about 5.3 × 5.3 Å 2 .…”
Section: Coordinative Guestsmentioning
confidence: 99%
“…The rational design and synthesis of complexes have received extensive attentions for their various intriguing architectures and potential applications [1][2][3][4]. Nevertheless, how to reasonably construct the desired structures is still a huge challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the assembly of metal−organic frameworks (MOFs) has become a very hot research topic because of their intriguing structural features and potential applications in a wide range of research fields such as gas storage/separation, 1−3 catalysis, 4 sensor, 5,6 and biomedical imaging. 7 Several strategies have been suggested for the rational construction of MOFs with desired structures and functions, in which reticular chemistry using the concept of secondary building units (SBUs) is demonstrated most popular and effective for this porpose.…”
Section: ■ Introductionmentioning
confidence: 99%